2019
DOI: 10.2116/analsci.19p359
|View full text |Cite
|
Sign up to set email alerts
|

A Fluorescent Sensor Based on Reversible Addition-Fragmentation Chain Transfer Polymerization for the Early Diagnosis of Non-small Cell Lung Cancer

Abstract: We proposed a novel, ultrasensitive and low-cost sensor using reversible addition-fragmentation chain transfer (RAFT) polymerization as a signal amplification strategy for the detection of CYFRA 21-1 DNA fragment, a tumor marker of non-small cell lung carcinoma. The peptide nucleic acid (PNA) probes were firstly immobilized on magnetic beads (MBs) to capture the CYFRA 21-1 DNA specifically. After hybridization, CPAD was tethered to the hetero duplexes through the carboxylate-Zr 4+ -phosphate chemistry.Subseque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Among them, CPAD and fluorescein-o-acrylate (FA) are used as CTAs and monomers of RAFT. [79] Next, in 2019, Sun et al [32] combined electrochemical-mediated RAFT with silver nano-plating technology to achieve a dual-signal amplification strategy for effective detection of target DNA. This method breaks the detection limit of a DNA biosensor based only on RAFT amplification strategy and can regulate the molecular weight range of RAFT products by controlling the magnitude of the externally applied voltage or current as shown in Figure 7B.…”
Section: Raft-mediated Dna Biosensormentioning
confidence: 99%
“…Among them, CPAD and fluorescein-o-acrylate (FA) are used as CTAs and monomers of RAFT. [79] Next, in 2019, Sun et al [32] combined electrochemical-mediated RAFT with silver nano-plating technology to achieve a dual-signal amplification strategy for effective detection of target DNA. This method breaks the detection limit of a DNA biosensor based only on RAFT amplification strategy and can regulate the molecular weight range of RAFT products by controlling the magnitude of the externally applied voltage or current as shown in Figure 7B.…”
Section: Raft-mediated Dna Biosensormentioning
confidence: 99%
“…Early detection of cancer is important for effective treatment, and many biomarker-based diagnostic methods have been reported 1 . Circulating microRNAs (miRNAs) in the body fluids serve as promising biomarkers for the early detection of cancer 2,3 .…”
Section: Introductionmentioning
confidence: 99%
“…Kong et al reported on an ultrasensitive sensor using reversible additionfragmentation chain transfer (RAFT) polymerization as a signal amplification strategy for the detection of CYFRA 21-1 DNA fragment. 9 They employed magnetic beads modified with peptide nucleic acid probes to specifically capture the CYFRA 21-1 DNA. Hybridization was followed by CPAD tethering to the duplexes, and fluorescent tags were introduced to the duplexes through RAFT polymerization.…”
mentioning
confidence: 99%